Beyond Petra : nabataean cultic and mortuary practices and the cultural heritage of the Negev and Edom - Tebes, Juan Manuel (2020)
Fil: Tebes, Juan Manuel. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Instituto de Investigaciones; Argentina